1392. Associations between Stigma and Physical and Mental Health in the U.S. Military HIV Natural History Study. (15th December 2022) - Schvey, Natasha; Hsieh, Hsing-Chuan; Illinik, Luca; Chu, Xiuping; Ganesan, Anuradha; Schofield, Christina; Colombo, Rhonda E; Berjohn, Catherine M; Okulicz, Jason; Agan, Brian
Abstract: Background: Despite increasing attention to HIV-related stigma within the DoD, to date, the majority of research has focused on civilians, up to half of whom report perceived or experienced stigma. However, military service members and retirees with HIV may be particularly vulnerable to stigma and its adverse correlates. Methods: The current study utilized cross-sectional data collected within the U.S. Military HIV Natural History Study. Participants completed questionnaires, including the Center for Epidemiologic Studies Depression scale, the Short Form Health Survey, the Internalization Subscale of the HIV Stigma Scale, and a measure of stigma experienced in the past year. Experiences of stigma were dichotomized to indicate presence or absence. Linear and logistic regressions were used to examine associations between internalized stigma and psychosocial functioning. All analyses were adjusted for age, race, sex, marital status, military rank, and duty status (i.e., active duty or retired). Results: The sample comprised 399 participants (93.5% male; 46.0% Black/African American; Mage : 50.8 ± 13.2 years; Mage at HIV diagnosis: 31.9 ± 8.2 years; 32.4% on active duty). The majority (94.4%) had an undetectable viral load at the time of the visit. Fourteen percent reported being teased, treated unfairly, or discriminated against in the past year due to their HIV status, and 8% reported discrimination specifically within healthcare. Adjusting for covariates, internalized stigma was associated with poor physical ( p < .001) and overall mental ( p < .001) health. Internalized stigma was also associated with greater odds of reporting elevated depression ( p < .001). Conclusion: In this sample of service members and retirees with HIV, a small but significant minority of participants reported experiencing stigma. Rates of stigma were lower than those observed in some civilian samples, though heterogeneity in sampling and methodology preclude direct comparisons. Internalized stigma was associated with poor physical and mental health, signaling a need for continued efforts to assess both experienced and internalized stigma. Future research should explore associations between stigma, ART adherence, and other metrics of health, such as CD4 count, substance use, and cardiometabolic risk. Disclosures: All Authors : No reported disclosures.